El concilio alejandrino de 339 y sus consecuencias - Fernández Hernández, Gonzalo (Estudios humanísticos. Geografía, historia y arte, 1999)
This article deals with the alexandrian council in year 339 A. D. and its consequences. Sources: Athanasius of Alexandria, Eusebius of Caesarea, George Cedrenus, Socrates and Theodoret of Cyr.